Efektivitas Terapi Murottal Al-Quran dalam Menurunkan Risiko Perilaku Kekerasan pada Pasien Skizofrenia di Panti Gramesia Cirebon - Ruswati Ruswati; Sofiyati Sofiyati; Dyah Sriwigati; Yolailah Haritsah; Berlian Ayu Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Schizophrenia is a chronic mental disorder that can cause changes in thoughts, emotions, and behavior. According to WHO (2022), there are 24 million people with schizophrenia worldwide, with a prevalence in Indonesia of 1.8 per 1,000 population. At Panti Gramesia Cirebon, 24 patients were recorded as having a risk of violent behavior. Purpose: To obtain a real-life overview of providing nursing care to Mr. H with the nursing problem of risk of violent behavior due to schizophrenia. Method: The study used a case study design with data collection through observation, interviews, and documentation. The case study subject was one patient with a risk of violent behavior. Results: Implementation was carried out over three days and showed that the patient experienced progress. Initially, the patient showed a high drive for violence, such as threats or self-harm. However, after interventions, the patient showed a significant reduction in violent urges, with improved ability to control emotions and aggressive behavior. This indicates that the combination of pharmacological therapy and non-pharmacological therapy using Quran Murottal Therapy was effective in helping the patient manage violent behavior. Conclusion: This shows that collaboration between pharmacotherapy, implementation strategies, and Quran Murottal Therapy is effective in reducing aggressive behavior and symptoms of risk for violent behavior.